2017
DOI: 10.1073/pnas.1617721114
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation-accelerated neuronal regeneration following selective rod photoreceptor cell ablation in the zebrafish retina

Abstract: Müller glia (MG) function as inducible retinal stem cells in zebrafish, completely repairing the eye after damage. The innate immune system has recently been shown to promote tissue regeneration in which classic wound-healing responses predominate. However, regulatory roles for leukocytes during cellular regeneration-i.e., selective cell-loss paradigms akin to degenerative disease-are less well defined. To investigate possible roles innate immune cells play during retinal cell regeneration, we used intravital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
236
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 159 publications
(271 citation statements)
references
References 84 publications
(145 reference statements)
33
236
1
1
Order By: Relevance
“…The ARQiv-HTS platform was used to screen compounds for neuroprotective effects in a transgenic zebrafish model of RP, Tg(rho:YFP-Eco.NfsB)gmc500, hereafter, rho:YFP-NTR (Walker et al, 2012;White et al, 2017). In this line, a 3.7 kb rhodopsin (rho) promoter fragment (Hamaoka et al, 2002) drives transgene expression exclusively in rod photoreceptor cells.…”
Section: Establishing a Large-scale Neuroprotectant Screen Using An Imentioning
confidence: 99%
See 3 more Smart Citations
“…The ARQiv-HTS platform was used to screen compounds for neuroprotective effects in a transgenic zebrafish model of RP, Tg(rho:YFP-Eco.NfsB)gmc500, hereafter, rho:YFP-NTR (Walker et al, 2012;White et al, 2017). In this line, a 3.7 kb rhodopsin (rho) promoter fragment (Hamaoka et al, 2002) drives transgene expression exclusively in rod photoreceptor cells.…”
Section: Establishing a Large-scale Neuroprotectant Screen Using An Imentioning
confidence: 99%
“…Having extensive MOA data is a key advantage afforded by testing human-approved compounds which we leveraged in a previous large-scale zebrafish PDD screen (G. . Similarly here, as studies have suggested inflammation plays a key role in retinal degeneration and regeneration (Hollyfield et al, 2008;Mitchell et al, 2018;White et al, 2017;Yoshida et al, 2013), hits implicated as modulators of inflammatory signaling were included. In addition, several compounds that did not produce concentrationdependent effects were selected to test whether this criterion was useful in predicting reproducibility.…”
Section: Validation Assay I: Confirmationmentioning
confidence: 99%
See 2 more Smart Citations
“…An overwhelming amount of literature supports that microglia contribute to pathological changes through secretion of proinflammatory cytokines leading to cytotoxicity (Chen & Xu, 2015;Madeira, Boia, Santos, Ambrosio, & Santiago, 2015;McVicar et al, 2015;Murinello et al, 2014;Perry & Holmes, 2014;Zhang et al, 2012). However, few recent studies have shown that in certain instances, microglia activation can be protective (Chuang et al, 2016;Holtman et al, 2017;Le, Wu, & Tang, 2016;White et al, 2017). With regard to ischemic injury of the CNS, microglia depletion has been shown to induce more severe ischemic neuronal damage (Szalay et al, 2016).…”
Section: Endothelial Cells Of Both the Retinal And Choroidal Vasculatmentioning
confidence: 99%